Bridging the partisan divide self-affirmation reduces ideological closed-mindedness and inflexibility in negotiation [article]. - Cohen, Jeffrey L.
Three studies link resistance to probative information and intransigence to concerns of identity maintenance. It shows that affirmations of personal integrity (vs. nonaffirmation or threat) can reduce resistance and intransigence but this effect occurs only when individuals' partisan identity and.or identity-related convictions are made salient. Affirmation made participants' assessment of a report critical of U.S. foreign policy less dependent on their political views,but only when the identity relevance of the issue rather than the goal of rationality was salient (Study 1). Affirmation increase concession making in a negotiation over abortion policy, but again this effect was moderated by identity salience (Studies 2 and 3). Indeed, although affirm negotiators proved relatively more open to compromise when either the salience of their true convictions or the importance of remaining faithful to those convictions was heightened, the reverse was true when the salience goal was compromise. The theoretical and applied significance of these findings are discussed.